OPTIMIZATION OF FUNCTION OF TWO VARIABLES, A NUMERICAL APPROACH - Wiryanto, Leo Hari; Djohan, Warsoma (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2024)
Teaching development in maximum value of a function of two variables is reported in this paper. Based on an experience in teaching numerical method, difficulty in determining step size of steepest ascent gives an idea to covert the function into one variable, so that we can solve numerically by standar method for that function, such as Newton method. Here, we present some examples to support that development.